Outcome Prediction in Patients of Traumatic Brain Injury Based on Midline Shift on CT Scan of Brain - Palekar, Shrikant Govindrao; Jaiswal, Manish; Patil, Mandar; Malpathak, Vijay (Indian Journal of Neurosurgery, 2021)
Background Clinicians treating patients with head injury often take decisions based on their assessment of prognosis. Assessment of prognosis could help communication with a patient and the family. One of the most widely used clinical tools for such prediction is the Glasgow coma scale (GCS); however, the tool has a limitation with regard to its use in patients who are under sedation, are intubated, or under the influence of alcohol or psychoactive drugs. CT scan findings such as status of basal cistern, midline shift, associated traumatic subarachnoid hemorrhage (SAH), and intraventricular hemorrhage are useful indicators in predicting outcome and also considered as valid options for prognostication of the patients with traumatic brain injury (TBI), especially in emergency setting.Materials and Methods 108 patients of head injury were assessed at admission with clinical examination, history, and CT scan of brain. CT findings were classified according to type of lesion and midline shift correlated to GCS score at admission. All the subjects in this study were managed with an identical treatment protocol. Outcome of these patients were assessed on GCS score at discharge.Results Among patients with severe GCS, 51% had midline shift. The degree of midline shift in CT head was a statistically significant determinant of outcome (p = 0.023). Seventeen out of 48 patients (35.4%) with midline shift had poor outcome as compared with 8 out of 60 patients (13.3%) with no midline shift.Conclusion In patients with TBI, the degree of midline shift on CT scan was significantly related to the severity of head injury and resulted in poor clinical outcome.
Keywords: traumatic brain injury; midline shift in CT scan brain; Glasgow coma scale